2006
DOI: 10.1097/01.ajp.0000169675.41815.49
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Cement Injection into a Created Cavity for the Treatment of Vertebral Body Fracture

Abstract: The Cavity Creation System is a safe, cost-effective treatment of VBF resulting in good/excellent pain relief and an improved quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Now that the Kyphon device is off patent, there are legions of copycat devices available from most manufacturers. A modified procedure employs reusable hingedtip curet to manually create a cavity in fractured vertebral bodies under fluoroscopy guidance, allowing low resistance injection of more viscous cement [82] . We have often used a similar curet to create space for the balloon when the hardness of the vertebral body prevented the balloon from creating a cavity of the appropriate size.…”
Section: Future Developmentsmentioning
confidence: 99%
“…Now that the Kyphon device is off patent, there are legions of copycat devices available from most manufacturers. A modified procedure employs reusable hingedtip curet to manually create a cavity in fractured vertebral bodies under fluoroscopy guidance, allowing low resistance injection of more viscous cement [82] . We have often used a similar curet to create space for the balloon when the hardness of the vertebral body prevented the balloon from creating a cavity of the appropriate size.…”
Section: Future Developmentsmentioning
confidence: 99%
“…However, using the screw-syringe pressure application, which increases the pressure that is applied to the cement, may introduce additional risks of leakage due to the loss of tactile feedback of cement delivery and the higher injection pressure. To overcome the limitations of vertebroplasty associated with the excessive pressure required to inject suffi cient cement into a fractured body, can-nulae have been designed with larger proximal portion internal diameters [21] and a reusable hinged-tip curet to manually create a cavity was employed [22] . The modifi ed vertebroplasty technique described in the present study creates small cavities and micro-connections with the fracture gaps in the vertebral body using a curved probe.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, leak rates should not be compared between studies without mentioning the method of leak detection. There have been various reports on techniques for leak rate reduction in vertebroplasty [23,24]. Using a Fogarty balloon inflation for hole creation, Schulte et al [24] reported epidural cement leaks in 9.1% and intradiscal leaks in 10.6%.…”
Section: Discussionmentioning
confidence: 99%